Microstructure of Z-phase strengthened martensitic steels: Meeting the 650°C challenge - LAWITZKI, ROBERT (My University, 2016)
This work aids the development of a new generation of martensitic steels that enable working conditions of 650 °C / 350 bar. A new concept called Z-phase strengthen-ing is applied, where the thermodynamically most stable phase in these steels, Z-phase, is used as the strengthening agent. These steels have a great potential to increase the thermal efficiency of fossil fired steam power plants, decrease their CO2 emissions, and enhance their operational flexibility to better accommodate ener-gy generation from renewable sources. The microstructure of two Z-phase strengthened 9-12% Cr trial steels was studied. These two trial steel were designed to study three important issues: i) the effects of Mo addition on Laves-phase formation; ii) the effects of combining Nb and Ta on the Z-phase formation; iii) the effects of C content on the Z-phase formation. Scanning electron microscopy was used to follow the evolution of Laves phase parti-cle size, area fraction and number density in the these trial steels during aging at 600 °C, 650 °C, and 700 °C for up to 31 days. Compared with equilibrium calcula-tions obtained by JMatPro and ThermoCalc, it is shown that Laves phase has almost fully precipitated after 31 days of aging at 650 °C and 700 °C, but not for aging at 600 °C. These results were verified by matrix investigations using atom probe tomog-raphy. Furthermore, atom probe tomography was used to investigate the evolution of the chemical compositions of carbonitrides and Z-phase during aging. The results show that Z-phase forms faster in carbonitrides with high nitrogen to carbon, and ni-obium to tantalum ratios.
Keywords: Energi; Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Energy; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Mechanical Engineering